Faktor Gaya Hidup sebagai Prediktor Kualitas Hidup pada Pasien Luka Kaki Diabetik: Studi Cross-Sectional di Indonesia - Restu Anisa Putri; Rani Sauriasari; Atika Wahyu Puspitasari (Jurnal Ners, 2026)
Diabetic foot ulcers (DFUs) are a serious complication of diabetes mellitus (DM) that significantly impacts patients' quality of life. Lifestyle factors, particularly smoking status and physical activity, are important modifiable factors to support improvement of this condition. This study aims to analyze the relationship between these two factors and the quality of life of DFU patients in Indonesia. A predictive cross-sectional study was conducted on 70 patients undergoing treatment at six branches of the Diabetic Wound Care Home Clinic in the Greater Jakarta area during March–May 2025. Quality of life was measured using the Indonesian version of the Diabetic Foot Ulcer Scale-Short Form (DFS-SF). Analysis was performed using the chi-square test for bivariate associations and multivariate logistic regression, controlling for confounding variables. The results showed that most patients did not smoke (74.3%) and did not exercise regularly (70.0%). Smoking status was significantly associated with quality of life (p=0.042), while physical activity showed a trend towards significance (p=0.060). Multivariate analysis identified physical activity as a predictor of quality of life (OR=5.30; 95% CI: 0.96–29.14; p=0.055), with patients who did not exercise being 5.3 times more likely to experience low quality of life. Smoking status showed a paradoxical result (OR=0.12; 95% CI: 0.02–0.82; p=0.030), which requires cautious interpretation. Physical activity also significantly impacted the domains of dependency/activities of daily living (p=0.001) and physical health (p=0.002). These findings emphasize the importance of integrating physical activity promotion and healthy lifestyle interventions in the holistic management of patients with LKD to support improved quality of life.